The London library: an interview with Dunia Garcia-Ontiveros and Gill Turner. (Perspectivas em Ciência da Informação, 2017)
On February 17th, 2017 I had the opportunity to visit The London Library with my friend Judith Hodgson, an English specialist on rare books and a habitual user of this library. I would like to thank her and also thank the librarians Dunia Garcia – Ontiveros, Head of Bibliographic Services and Gill Turner, Head of Acquisitions....